Persistence of a Stx-Encoding Bacteriophage in Minced Meat Investigated by Application of an Improved DNA Extraction Method and Digital Droplet PCR - Spilsberg, B.; Sekse, C.; Urdahl, Anne M.; Nesse, Live L.; Johannessen, Gro S. (Frontiers in Microbiology, 2021)
Shiga toxin-producing Escherichia coli (STEC) are important food-borne pathogens with Shiga toxins as the main virulence factor. Shiga toxins are encoded on Shiga toxin-encoding bacteriophages (Stx phages). Stx phages may exist as free bacteriophages in the environment or in foods or as prophages integrated into the host genome. From a food safety perspective, it is important to have knowledge on the survival and persistence of Stx phages in food products since these may integrate into the bacterial hosts through transduction if conditions are right. Here, we present the results from a study investigating the survival of a Stx phage in minced meat from beef stored at a suboptimal temperature (8°C) for food storage along with modifications and optimizations of the methods applied. Minced meat from beef was inoculated with known levels of a labeled Stx phage prior to storage. Phage filtrates were used for plaque assays and DNA extraction, followed by real-time PCR and digital droplet PCR (ddPCR). The results from the pilot study suggested that the initial DNA extraction protocol was not optimal, and several modifications were tested before a final protocol was defined. The final DNA extraction protocol comprised ultra-centrifugation of the entire phage filtrate for concentrating phages and two times phenol–chloroform extraction. The protocol was used for two spiking experiments. The DNA extraction protocol resulted in flexibility in the amount of DNA available for use in PCR analyses, ultimately increasing the sensitivity of the method used for quantification of phages in a sample. All three quantification methods employed (i.e., plaque assays, real-time PCR, and ddPCR) showed similar trends in the development of the phages during storage, where ddPCR has the benefit of giving absolute quantification of DNA copies in a simple experimental setup. The results indicate that the Stx phages persist and remain infective for at least 20 days under the storage conditions used in the present study. Stx phages in foods might represent a potential risk for humans. Although it can be speculated that transduction may take place at 8°C with subsequent forming of STEC, it can be expected to be a rare event. However, such an event may possibly take place under more optimal conditions, such as an increase in storage temperature of foods or in the gastrointestinal tract of humans.